Academics’ Perceptions of the Principles for Responsible Management Education (PRME) for Sustainable Development - Boodhoo, Suvera; Parumasur, Sanjana Brijball (Journal of Economics and Behavioral Studies, 2017)
In light of business leaders’ failings, including corporate corruption, the financial crisis and various ecological system crises there is a growing expectation that management education institutions should be leading thought and action on issues related to corporate responsibility and sustainability. Therefore, there is a need to ascertain management education institutions’ ability to ensure responsible and sustainable management education. This paper seeks to assess academics’ perceptions of how the University of KwaZulu-Natal has adopted the United Nation (UN) supported initiative, Principles for Responsible Management Education (PRME), to ensure responsible and sustainable management education in South Africa. The sample was drawn using the probability sampling technique called cluster sampling. Permanent academic staff from the Graduate School of Business and Leadership and the School of Management, Information Technology and Governance who responded to the structured, self-administered questionnaire formed the sample. Questions asked related to fostering a sustainable culture, strategically adapting curriculum, creating learning environments, aligning research, fostering sustainable partnerships and encouraging constant dialogue with regards to PRME. In order to assess the implementation of the PRME for sustainable development, a quantitative research design was adopted. This is the first study, to the researcher’s knowledge, to examine the University of KwaZulu-Natal’s Graduate School of Business and Leadership and the School of Management, Information Technology and Governance’s motives, effects and challenges of engaging in PRME. The study has also explored key aspects such as the adaptation of teaching practices by the academic staff, the role of academics and diversification that influences the decision of the Graduate School of Business and Leadership and School of Management, Information Technology and Governance to participate in PRME. The results indicate that academic staff in both schools is engaging in activities that pursue the cause of sustainable development. There is evidence of addressing modern societal and environmental challenges by fostering change in design in curricula, fostering a sustainable culture and creating a learning environment. However, evidently more careful and deliberate attention needs to be given to fostering constant dialogue and aligning PRME and research to enhance economic, environmental and social development. This study provides a model/framework to present current practices and obstacles/setbacks experienced in adopting PRME and will present recommendations to facilitate the adoption of PRME by UKZN.